Stabilization effect of distributed delay with strong kernel in three-neuron BAM neural networks - Mandal, Santanu; Dasgupta, Poulami; Roy, A; Majee, N (International Journal of Applied Mathematical Research, 2014)
The effect of distributed delays with strong kernel in the dynamics in three-neuron BAM neural network model is studied. Instead of destabilization phenomena this neural systems become asymptotically stable through Hopf bifurcation with the gradual increment of mean delay. Existence of Hopf bifurcation is studied in frequency domain. Direction and stability of Hopf bifurcating periodic solutions are analyzed using Nyquist criterion and graphical Hopf bifurcation theorem.   Keywords: Distributed delay, Hopf bifurcation, Frequency domain, Stabilization effect, Strong kernel